(untitled) - Biegel, Kenneth (New York, 2002)
"What About You?" is a new two-level series that teaches young adult and adult students how to maintain and extend a conversation in English. Once students have mastered basic speaking skills, the series will teach them conversational strategies, such as how to start and end a conversation, and how to take turns throughout a conversation."What About You?" encourages pairwork and groupwork and is great to use with large or multi-level classes. Teachers can easily monitor and assess their students" progress with the help of progress reviews and quizzes that appear regularly throughout the series. Thus, Book 1 (Low-intermediate to Intermediate) and Book 2 (Intermediate to High-Intermediate) address the wide range of ability within a classroom. The speaking activities in both books furnish the structure that the less able students need while providing the opportunity for the more able students to expand response and exchange. Additional features to the book are as follows: Every fourth reviews the previous three. Crossword puzzles and games engage the learners. Topics are true to life and of interest to young adults - vocabulary and structures reflect the topics and themes. This study includes 36 to 60 hours of instructional material. English functions are stressed.
Keywords: English language,Tiếng Anh; Textbooks for foreign speakers,Giáo trình dành cho người nước ngoài